Judicial governance as an effective solution to orality in Brazilian civil process: sustainable jurisdiction (Research, Society and Development, 2021)
Full oral litigation is not foreseen in Brazil, but is adopted in certain acts. However, many times this institute is applied unevenly, or is not even applied, since the law generally establishes a faculty as to its use. For this reason, a debate is indispensable in order to criticize this use by the subjects of the process. For this, the legal-theoretical method and deductive reasoning were used, with bibliographic research technique. In the end, it is concluded that judicial governance can be an effective means, not with regard to the effectiveness of orality and, consequently, the effectiveness of jurisdiction.